HUBUNGAN KELINCAHAN DENGAN KETEPATAN MENGGIRING BOLA PADA SISWA KELAS VIII SMP MUHAMMADIYAH KUOK - friyontoni, Dedi; ', Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of student in class VII SMP Muhammadyah Kuok. Researcher found many student have deficiency of dribbling, visible when the student dribble imperfect, as the ball away from the feet. The purpose of this research is to the correlation of agility and accuracy dribbling ball of student in class VII SMP Muhammadyiah Kuok. Population in this research is all students in class VII SMP Muhamadiyah Kuok amount 25 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 25 people. Research instrument used dogging run test to agility and dribbling ball test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is correlation agility and accuracy dribbling ball of male students class VII SMP Muhamadiyah Kuok, which shows rhitung = 0,587> rtab 0,576. there is correlation agility and accuracy dribbling ball of female student in grade VII Muhamadiyah Kuok Junior High School, which shows rhitung = 0,709> rtab 0,602.Key word : Agility, Dribbling.